FR2.3: Women's Voices in Civil Society Organizations: Evidence from a Civil Society Mapping Project in Mali - Kosec, Katrina; Bleck, Jaimie; Gottlieb, Jessica (International Food Policy Research Institute, 2022)
How does women's engagement in civil society organizations (CSOs) differ from that of men, and what factors predict women's willingness to hold the state accountable? We analyze these questions in the context of rural and urban Mali, leveraging face-to-face data collected as part of a civil society mapping project during February-March 2020 and December 2020, and an in-depth survey conducted with leaders from a randomly-selected subset of these CSOs during January -- March 2021. First, we explore the characteristics of women's groups compared to other CSOs. Second, we explore their likelihood of sanctioning a hypothetical corrupt mayor. We use an embedded survey experiment to try to understand these groups' willingness to report on the mayor. We find that women in Mali are often highly organized at the local level with great mobilization capacity than men--frequently in self-help groups or organizations related to gendered economic activities. However, they are not typically recognized by outside actors; their strong networks and group infrastructure represent untapped social capital. CSOs comprised of women have lower informational and technical capacity, including lower levels of political knowledge, and incur a higher cost of sanctioning public officials. Women are generally less willing than men to sanction, but become more likely when their CSO is less hierarchical, when their technical capacity is higher, and when their political knowledge is greater. However, priming their importance as a CSO (by telling them they were identified by well-connected citizens as influential) reduces sanctioning--perhaps by making them fear reprisals from recommenders.